Tests of demountable reinforced concrete slabs. (December 2022) - Almahmood, Hanady; Ashour, Ashraf; Figueira, Diogo; Yıldırım, Gurkan; Aldemir, Alper; Sahmaran, Mustafa
Abstract: This paper presents an experimental investigation of demountable reinforced concrete slabs using dry connections between reinforced concrete slab elements. The test specimens comprised six full-scale reinforced concrete slabs; one control slab monolithically cast, while the other five slabs were produced with mid-span demountable dry connections. The slab elements were cast separately and assembled using top and bottom steel plates joined to each side of the slab element by high tensile steel bolts with or without a shear key and embedded steel block. Theoretical analysis of the behaviour of the demountable slabs tested in comparison with the control specimen was also conducted. The test results showed that using a dry connection consisting of a shear key at the assembled section is the most effective technique in terms of moment resistance, deflection, and flexural stiffness. On the other hand, the dry connection with embedded steel blocks failed prematurely because of stress concentration at the block edges. The moment capacity and deflection predictions of demountable slabs have reasonably correlated with the experimental results but required additional calibrated data from experiments.